Anacardic acid suppresses fibroblast-like synoviocyte proliferation and invasion and ameliorates collagen-induced arthritis in a mouse model. (November 2018) - Yang, Guo-hui; Zhang, Chi; Wang, Nan; Meng, Yu; Wang, Yi-sheng
Abstract: Anacardic acid, which is abundant in nutshell of Anacardium occidentale, has multiple pharmacological activities. In this study, we examined the therapeutic potential of anacardic acid in treating rheumatoid arthritis (RA). We explored the effects of anacardic acid on collagen-induced arthritis (CIA) in mice and on the proliferation and invasion of RA fibroblast-like synoviocytes (RA-FLSs). The underlying molecular mechanism was investigated. Anacardic acid treatment markedly suppressed paw swelling, joint destruction, and arthritis scores in CIA mice. The serum levels of tumor necrosis factor alpha (TNF- α) and interleutkin-1beta (IL- 1β) were significantly lowered by anacardic acid. In vitro assays demonstrated that anacardic acid impaired the proliferation and invasion abilities of RA-FLSs in the presence of TNF- α or IL- 1β. Western blot analysis revealed the reduction of Akt protein expression and phoshporylation in RA-FLSs by anacardic acid. However, the mRNA level of Akt remained unchanged. Anacardic acid treatment significantly increased the expression of miR-633 in RA-FLSs. Akt was identified as a novel target of miR-633. Overexpression of miR-633 significantly inhibited the proliferation and invasion of RA-FLSs, which was rescued by enforced expression of Akt. Depletion of miR-633 prevented anacardic acid-mediated suppression of proliferation and invasion of RA-FLSs, which was accompanied by increased expression of Akt protein. In conclusion, anacardic acid may serve as a promising agent in the treatment of RA.